MATISSE first pictures of dust and molecules around R Sculptoris. Issue Volume 16:Issue S366(2020) (November 2020) - Drevon, J.; Millour, F.; Cruzalèbes, P.; Paladini, C.; Hron, J.; Meilland, A.; Allouche, F.; Aringer, B.; Berio, P.; Danchi, W.C.; Hocdé, V.; Hofmann, K.-H.; et al.
Abstract: Carbon-rich dust is known to form in the atmosphere of the semiregular variable star R Sculptoris. Such stardust, as well as the molecules and gas produced during the lifetime of the star, will be spread into the Galaxy via the mass-loss process. Probing this process is crucial to understand the chemical enrichment of the Galaxy. R Scl was observed using the ESO/VLTI MATISSE instrument in December 2018. Here we show the first images of the star between 3 and 10 R * . Using the complementary MIRA 3D image reconstruction and the RHAPSODY 1D intensity profile reconstruction code, we reveal the location of molecules and dust in the close environment of the star. Indeed, the C2 H2 and HCN molecules are spatially located between 1 and 3.4 R * which is much closer to the star than the location of the dust. The R Scl spectrum is fitted by molecules and a dust mixture of 90% of amorphous carbon and 10% of silicone carbide. The inner boundary of the dust envelope is estimated by DUSTY at about 4.6 R * . We derive a mass-loss rate of 1.2 ± 0.4 × 10 −6 M ⊙ yr −1 however no clear SiC forming region has been detected in the MATISSE data.